Preliminary Study on Antibacterial Activity of Sawo Kecik (Manilkara kauki (L.) Dubard) Roots Extract - Pratiwi, Novida; Retnosari, Rini; Prabaningtyas, Sitoresmi (Jurnal Biodjati, 2021)
The roots of sawo kecik (Manilkara kauki (L.) Dubard) containÂ astringent that can be used to treat diarrhea for infants. However, the active antibacterial substance in sawo kecik roots has not been known. Therefore, the research to understand the antimicrobial activity of sawo kecik roots extract against Escherichia coli and Staphylococcus aureus wasÂ performed. Sawo kecik roots wereÂ macerated using methanol and chloroform. The result was then treated withÂ E.coli and S.aureus with aÂ concentration of 5 ppm and compared to negative control (solvent) and further observed and analyzed how reduced the bacterial growth with Two Ways ANOVAÂ without interaction. The research resultsÂ indicated that the sawo kecik roots methanol extract was effective to slow down the growth of S.aureusÂ (0.160Â Â± 0.007) butÂ ineffective against E.coli, whereas sawo kecik roots chloroformÂ extract was not effective to reduce both bacteria. It can be concluded that further research is required to measure and verify the antibacterial activity of the extract using higher concentration samples and different research methodology.